Valoración agronómica de cinco accesiones de trigo (Triticum aestivum), en el tercer periodo de evaluación, en Laguacoto, provincia Bolívar - Urrea Ledesma, Jhomayra Lizbeth (2024)
Wheat is a basic and essential agricultural product in the food field worldwide. It is one of the most important crops in the mountains of Ecuador, constitutes part of the basic basket for small producers in the region. the province of Bolívar is part of the production systems of small and medium producers, mainly in rotation after corn associated with beans. The research trial was located in the Laguacoto III Experimental Farm sector of the UEB, the general objective: To evaluate five wheat accessions agronomically, in the third evaluation period, the research a Randomized Complete Block Design (DBCA) with five treatments and three repetitions was used. An analysis of variance, the 5% Tukey test was applied to compare the averages between the accessions, evaluation analysis and linear regression and performance with the significant variables. In the analysis of reaction to foliar diseases (p. striiformis), a general average of 4.67% was obtained. The treatment that showed the greatest resistance to said disease was T1, which identified the accession TA-18-008 with 0%. severity. For BYDV, a general average of 2.73% was obtained. The average general grain yield between accessions was 2865.34 kg/ha. The treatment with the highest yield is T4 with 3431.55kg/ha and treatments T1 with 2654.61 kg/ha, T2 with 2362.71 kg/ha are the accessions that present the lowest yield